Kaposiform lymphangiomatosis treated with multimodal therapy improves coagulopathy and reduces blood angiopoietin‐2 levels. Issue 9 (7th July 2020) - Crane, Janet; Manfredo, Jackie; Boscolo, Elisa; Coyan, Mara; Takemoto, Clifford; Itkin, Maxim; Adams, Denise M.; Le Cras, Timothy D.
Abstract: Kaposiform lymphangiomatosis (KLA) is a rare, life‐threatening congenital lymphatic malformation. Diagnosis is often delayed due to complex indistinct symptoms. Blood angiopoietin‐2 (ANG2) levels are elevated in KLA and may be useful as a biomarker to monitor disease status. We report a 7‐year‐old male child with easy bruising, inguinal swelling, and consumptive coagulopathy, diagnosed with KLA. A multimodal treatment regimen of prednisone, sirolimus, vincristine, and adjunctive zoledronate was used. Plasma ANG2 levels were highly elevated at diagnosis but decreased during treatment. The patient showed significant clinical improvement over a 38‐month period and normalization of ANG2 levels correlated with resolution of the coagulopathy.